Sidelights on Greek antiquity: archaeological and epigraphical essays in honour of Vasileios Petrakos - Kalogeropulos, Kōnstantinos; Basiliku, Ntora; Tiberios, Michalēs A.; Camp, John McK; Chaniotis, Angelos; Clinton, Kevin; Davis, Jack L; Ducrey, Pierre; Fittschen, Klaus; Greco, Emanuele; Hatzopoulos, Miltiades B; Kalogeropulos, Kōnstantinos; et al. (De Gruyter, 2021)
Frontmatter -- Preface -- Contents -- List of Figures -- Tabula Gratulatoria -- Vasileios Petrakos: A Life Dedicated to the Service of Greek Archaeology -- Part I: Epigraphy and Ancient History -- Thucydides, Historical Geography and the ‘Lost Years’ of Perdikkas II -- Athens, Samothrace, and the Mysteria of the Samothracian Great Gods -- De quelques épitaphes d’étrangers et d’étrangères au Musée d’Érétrie -- Φυτωνυμικά τοπωνύμια Κωμών της Αργολίδος -- Le recours à l’arbitrage privé dans les actes d’affranchissement delphiques -- Προξενικό ψήφισμα από την Αιτωλία -- Women’s Religion in Hellenistic Athens -- Notes on Athenian Decrees in the Later Hellenistic Period -- “Those Who Jointly Built the City” -- Part II: Archaeology -- Attica and the Origins of Silver Metallurgy in the Aegean and the Carpatho-Balkan Zone -- Cultural Variation in Mycenaean Attica. A Mesoregional Approach -- Mythical and Historical Heroic Founders: The Archaeological Evidence -- Das Volutenkapitell aus Sykaminos -- Dionysos Lenaios at Rhamnous. Lenaia ἐν ἀγροῖς and the “Lenaia vases” -- Philoktet in Attika -- Part III: History of Greek Archaeology -- Peiraieus in 1805 -- Karl Otfried Müller in Marathon, Rhamnus und Oropos -- Spyridon Marinatos and Carl Blegen at Pylos: A Happy Collaboration -- Vassilis Petrakos et les fouilles suisses d’Érétrie -- List of Contributors -- Index of Epigraphical Texts -- Index Locorum -- Index of Mythological Names -- Index of Geographic Names (Place Names, Ethnic and Demotic Adjectives) -- Index of Ancient Personal Names -- Index Rerum -- Index of Modern Personal Names
Keywords: Festschrift; Epigraphik; Archäologie; Griechenland; Geschichte